2013
DOI: 10.1177/0261927x13502654
|View full text |Cite
|
Sign up to set email alerts
|

Pronoun Use Reflects Standings in Social Hierarchies

Abstract: Five studies explored the ways relative rank is revealed among individuals in small groups through their natural use of pronouns. In Experiment 1, four-person groups worked on a decision-making task with randomly assigned leadership status. In Studies 2 and 3, two-person groups either worked on a task or chatted informally in a get-to-know-you session. Study 4 was a naturalistic study of incoming and outgoing e-mail of 9 participants who provided information on their correspondents’ relative status. The last s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
344
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(372 citation statements)
references
References 35 publications
23
344
3
2
Order By: Relevance
“…The downside, however, is that such personable language may have reinforced the Twitter user's lack of social status and called his or her competence into question. 10,11 Although women used "I" more than did men, our results showed no meaningful differences in "I" use between men and women actors with many followers, a finding that is in contrast to documented literature using multiple samples indicating that women use the first person-pronoun more often than do men. 1,3 Although many LIWC studies use populations not limited to college-aged students, 8,18 most include a preponderance of persons in the college-age range whereas our sample did not.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The downside, however, is that such personable language may have reinforced the Twitter user's lack of social status and called his or her competence into question. 10,11 Although women used "I" more than did men, our results showed no meaningful differences in "I" use between men and women actors with many followers, a finding that is in contrast to documented literature using multiple samples indicating that women use the first person-pronoun more often than do men. 1,3 Although many LIWC studies use populations not limited to college-aged students, 8,18 most include a preponderance of persons in the college-age range whereas our sample did not.…”
Section: Discussioncontrasting
confidence: 99%
“…7,8 In contrast, use of "you" in social media is a marker of people who are open and conscientious. 9 First-person pronouns are more common in the language of people of lower status, 10 and they also decrease judgments of a speaker's competence.…”
Section: Pennebakermentioning
confidence: 99%
“…People in power seek to influence others through linguistic and paralinguistic means that convey confidence, decisiveness, and competence (Kacewicz et al 2013). Observations of communication in teaching contexts and organizations, eyewitness testimony, and experimental conditions found that, compared to the powerless, powerful people use more plural (we) than singular (I) pronouns (Kacewicz et al 2013) and tend to use fewer disclaimers (e.g., "I don't really know"), hesitations, hedges ("sort of," "maybe"), tag questions ("it is very cold out today, isn't it"), and intensifiers (e.g., "so;" Reid & Ng 1999, Thomas et al 2004). Together, these means of verbal communication effectively affect perceptions of status and power in observers, increasing persuasion and ability to attain desired ends (wanting and seeking).…”
Section: Power Energizes Thought Speech and Actionmentioning
confidence: 99%
“…People reveal a wealth of information about their feelings and intentions through verbal communication (8)(9)(10). The speaker's underlying motives notwithstanding, talking about helping others makes positive impressions upon an audience (11).…”
mentioning
confidence: 99%